Pengaruh Penggunaan Sistem Informasi Kepegawaian Terhadap Kualitas Pelayanan Administrasi di Sektor Publik - Syahrul Waldi; Pitri Andini; Rido Ilahi; Yulia Hanoselina (Perspektif Administrasi Publik dan hukum, 2024)
The Personnel Management Information System (SIMPEG) is a technology-based application used to manage personnel data in a centralized, efficient, and accurate manner. SIMPEG enables various administrative processes, such as payroll, promotions, and employee data management, to be automated, which were previously done manually and prone to errors. This study discusses the concept of SIMPEG, its implementation stages, and its benefits in improving efficiency, data accuracy, service transparency, quick decision-making, and centralized resource management. The research findings show that SIMPEG reduces manual workload, enhances the accuracy and speed of access to employee data, and supports better and more timely decision-making. In addition, SIMPEG increases transparency in administrative processes, reduces operational costs, and strengthens public trust in government institutions. However, the successful implementation of SIMPEG depends on the readiness of technological infrastructure and user training. Therefore, infrastructure development and training are crucial to optimizing SIMPEG use throughout Indonesia.